Theranostics: Magnetic Liposomal Particles for Magnetic Imaging, Sensing, and the pH‐Sensitive Delivery of Therapeutics (Part. Part. Syst. Charact. 5/2016). (May 2016) - Kwon, Yong‐Su; Jang, Su Jin; Yoon, Young Il; Cho, Hee‐Sang; Lee, Hak Jong; Cho, Young‐Seok; Shin, Hyun Soo; Yoon, Tae‐Jong
Abstract : Magnetic iron oxide nanoparticles contained in a shell of mesoporous silica provide a means for magnetic imaging and pH‐sensitive drug delivery. On page 242 Y.‐S. Cho, H. S. Shin, T.‐J. Yoon and co‐workers describe successful stabilization of such a theranostic system in liposomes that are anchored to cancer‐specific antibodies. Cancer therapy will profit from this highly selective system that offers imaging‐guided drug delivery.